Polysulfide benzothiazole compound and preparation method thereof
The preparation of polysulfide benzothiazole compounds by low-temperature polymerization has solved the problem of complex preparation methods and insufficient utilization of carbon disulfide in the prior art, and achieved the efficient dispersion effect of polymers with a fused ring structure in the field of oil well cement.
Patent Information
- Application Number
- CN202510874117.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2045-06-27
AI Technical Summary
In the prior art, the preparation method of 2-mercaptobenzothiazole is complex and requires strict reaction conditions, and carbon disulfide has not been effectively utilized as an atmospheric pollutant, and there is a lack of a simple and efficient method of constructing polysulfide benzothiazole compounds.
The low-temperature polymerization reaction of alkali, difunctional thiol monomer, carbon disulfide and difunctional o-iodoniline monomer is adopted to prepare the polysulfide benzothiazole compound through the participation of a catalyst, and then purify and dry it after the reaction to form a polymer with a fused ring structure.
The prepared polysulfide benzothiazole compounds have good solubility and thermal stability. They have excellent dispersion effects as cement dispersants in the field of oil well cement, reducing the viscosity of cement slurry and improving fluidity.
Smart Images

Figure CN120365562A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical fields of polymer chemistry and materials science, and specifically relates to a polysulfurized benzothiazole compound and a preparation method thereof. Background Art
[0002] In recent years, more and more 2-thiobenzothiazoles have been designed and synthesized for biological evaluation. The reported biological activities of thiobenzothiazoles include: overcoming multi-drug resistance in cancer chemotherapy; inhibiting the enzyme activities of 5-lipoxygenase and biochemical enzymes; antagonizing CCR3 receptor activity; anti-tuberculosis activity, etc. The synthetic methods thereof have attracted extensive attention from chemists due to various biological and pharmacological activities. 2-Mercaptobenzothiazole is often used as a key intermediate for preparing 2-thiobenzothiazoles. They can react with alkyl halides under alkaline conditions and react with alcohols under Mitsunobu reaction conditions to form 2-alkylthiobenzothiazoles, or can be coupled with aryl halides and arylboronic acids under the catalysis of copper and iron to form 2-arylthiobenzothiazoles. The intermediate 2-mercaptobenzothiazole is traditionally prepared by the condensation of carbon disulfide with 2-aminothiophenol. However, since the reaction substrate 2-aminothiophenol is not easily obtained, and the preparation of thiobenzothiazoles requires multiple reaction steps and harsh reaction conditions, there is an urgent need to explore alternative methods.
[0003] Carbon disulfide is an industrially abundant and inexpensive raw material, which is used not only as an organic solvent in various industrial processes, but also as a sulfur source in organic synthesis for preparing various sulfur-containing organic compounds. Due to its ready availability, economic and renewable nature, carbon disulfide is also a promising C1 building block for constructing sulfur-containing polymers. Since carbon disulfide molecules are flammable and toxic and are one of the main pollutants in the atmosphere, the conversion of carbon disulfide monomers into polymers is of great significance for environmental protection and polymer science.
[0004] Amines can react with carbon disulfide in the presence of a base to form dithiocarbamates. Based on this, the research group of Ma Dawei reported a three-component reaction for the synthesis of 2-N-substituted benzothiazoles from carbon disulfide, amines, and 2-haloanilines under mild conditions (Angew. Chem. Int. Ed. 2011, 123(5): 1150–1153). It was thus speculated that if the nucleophile was replaced by a thiol, a similar transformation might occur to obtain 2-thiobenzothiazole. In the field of polymer synthesis, by changing the thiol monomer and 2-haloaniline into a bifunctional structure and conducting a polycondensation reaction with carbon disulfide, it is expected to construct poly(thiobenzothiazole) compounds with a novel structure. This polymer contains a fused ring structure and nitrogen and sulfur heteroatoms and has potential application prospects as a cement dispersant in the field of oil well cement. The above polymerization reaction of carbon disulfide, bifunctional thiol monomers, and bifunctional o-iodoaniline monomers has not been developed yet and is a novel polymerization reaction using the atmospheric pollutant carbon disulfide as a monomer. In addition, this reaction can simply, efficiently, and economically construct poly(thiobenzothiazole) compounds with a novel structure, which has important scientific significance and application value. Summary of the Invention
[0005] The object of the present invention is to provide a poly(thiobenzothiazole) compound. The poly(thiobenzothiazole) compound has good solubility and thermal stability. In addition, the present invention also provides a preparation method thereof at the same time.
[0006] The poly(thiobenzothiazole) compound of the present invention has a general structural formula as shown in formula (I): ; Wherein: n is an integer from 5 to 100; R1 is selected from any one of the following chemical structural formulas 1-2; R2 is selected from the following chemical structural formula 3; R3 is selected from any one of the following chemical structural formulas 4-6;
[0007] Wherein, * represents the substitution position.
[0008] The preparation method of the poly(thiobenzothiazole) compound of the present invention is one of Method 1 or Method 2; wherein: Method 1: Add a base, a bifunctional aliphatic thiol monomer, and an organic solvent into a polymerization tube, then dropwise add carbon disulfide for a low-temperature reaction. Subsequently, add a catalyst, a bifunctional o-iodoaniline monomer, and an organic solvent into the polymerization tube for a polymerization reaction. After the reaction is completed, purify and dry the product to obtain the poly(thiobenzothiazole) compound; Method 2: Under a nitrogen atmosphere, a catalyst, a base, and a bifunctional aromatic thiol monomer are added to a polymerization tube. Then, carbon disulfide and an organic solvent are added dropwise for a low-temperature reaction. Subsequently, a bifunctional o-iodoaniline monomer and an organic solvent are added to the polymerization tube for a polymerization reaction. After the reaction is completed, the product is purified and dried to obtain a polysulfurized benzothiazole compound.
[0009] Among them: The structural general formula of the bifunctional aliphatic thiol monomer is shown in Formula (Ⅱ): ; The structural general formula of the bifunctional aromatic thiol monomer is shown in Formula (Ⅲ): ; The structural general formula of the bifunctional o-iodoaniline monomer is shown in Formula (Ⅳ): ; In Formulae (Ⅱ)-(Ⅳ), R1 is selected from any one of the following chemical structural formulae 1-2; R2 is selected from the following chemical structural formula 3; R3 is selected from any one of the following chemical structural formulae 4-6; ; Among them, * represents the substitution position.
[0010] In Method 1 or Method 2, the organic solvent is N,N-dimethylformamide (DMF). The organic solvent used in the low-temperature reaction is the same as the organic solvent used in the polymerization reaction, and the volume ratio of the two is 1-2:1.
[0011] The catalyst in Method 1 or Method 2 is one or more of cuprous chloride, cuprous bromide, or cuprous iodide; preferably, the catalyst is one of cuprous chloride or cuprous bromide.
[0012] The dosage of the catalyst in Method 1 or Method 2 is 1-4 times the amount of substance of the bifunctional o-iodoaniline monomer.
[0013] The base in Method 1 or Method 2 is one or more of potassium carbonate, potassium phosphate, or cesium carbonate; preferably, the base is cesium carbonate.
[0014] The dosage of the base in Method 1 or Method 2 is 0.5-3 times the amount of substance of the bifunctional o-iodoaniline monomer.
[0015] In Method 1, the molar ratio of carbon disulfide, the bifunctional aliphatic thiol monomer to the bifunctional o-iodoaniline monomer is (1.8 ~ 2.6):(0.8 ~ 1.2):1.
[0016] In Method 2, the molar ratio of carbon disulfide, bifunctional aromatic thiol monomers to bifunctional o-iodoaniline monomers is (2.0 - 2.2) : 1 : 1.
[0017] In Method 1 or Method 2, the concentration of bifunctional o-iodoaniline monomers in the organic solvent is 0.15 - 0.3 mol / L.
[0018] In Method 1 or Method 2, the temperature of the low-temperature reaction is 10 - 30 °C, the reaction time is 0.5 - 2 h, the temperature of the polymerization reaction is 80 - 130 °C, and the reaction time is 3 - 36 h.
[0019] In Method 1 or Method 2, the purification and drying steps are as follows: the product after the polymerization reaction is dissolved in an organic solvent, filtered, and then the filtrate is added to one of methanol, n-hexane, petroleum ether, or diethyl ether for precipitation. The precipitate is collected, and finally the precipitate is vacuum dried to a constant weight; wherein: the organic solvent in the purification step is the same as the organic solvent in the reaction system, and the drying temperature is 90 °C.
[0020] Compared with the prior art, the present invention has the following characteristics: (1) For the poly(thiophenobenzothiazole) compounds described in the present invention, by introducing various functional groups, the prepared functionalized poly(thiophenobenzothiazole) compounds have good solubility and thermal stability. Moreover, the prepared poly(thiophenobenzothiazole) compounds contain fused ring structures and nitrogen and sulfur heteroatoms, and can be used as cement dispersants, having potential application prospects in the field of oil well cement. Mechanistically, the polymer dispersant molecules adsorb on the surface of cement particles, forming a polymer molecule adsorption layer, which changes the charge repulsive force and steric hindrance repulsive force between particles, reduces the flocculation of cement particles, decreases the viscosity of the cement slurry, improves the fluidity of the cement slurry, and makes the oil well cement easier to operate during the cementing process.
[0021] (2) For the preparation method of the poly(thiophenobenzothiazole) compounds described in the present invention, different atmospheres are used when aliphatic thiol and aromatic thiol monomers are selected to participate in the polymerization reaction, and the type of catalyst (monovalent copper) and the type of solvent (DMF) are crucial for the smooth progress of the polymerization reaction and the purity of the polymerization product.
[0022] (3) For the preparation method of the poly(thiophenobenzothiazole) compounds described in the present invention, the conditions are mild, the operation is simple, the reaction raw materials and catalysts are cheap and easily available, and can be directly purchased or prepared through simple reactions. The carbon disulfide used in the polymerization reaction has a wide source and low cost. Description of the Drawings
[0023] Figure 1 1H NMR spectrum of the poly(thiophenobenzothiazole) compound prepared in Example 1 of the present invention in deuterated dimethyl sulfoxide; Figure 2 The ultraviolet absorption spectrum of the poly(thiophenylene benzothiazole) compound prepared in Example 1 of the present invention; Figure 3 The ultraviolet absorption spectrum of the poly(thiophenylene benzothiazole) compound prepared in Example 3 of the present invention; Figure 4 The thermogravimetric analysis curve of the poly(thiophenylene benzothiazole) compound prepared in Example 1 of the present invention; Figure 5 The thermogravimetric analysis curve of the poly(thiophenylene benzothiazole) compound prepared in Example 3 of the present invention; Figure 6 The proton nuclear magnetic resonance spectrum of the polymer prepared in Comparative Example 2 of the present invention in deuterated dimethyl sulfoxide. Detailed implementation manners
[0024] The present invention will be further described below in conjunction with embodiments.
[0025] Example 1 The poly(thiophenylene benzothiazole) compound prepared in this Example 1 has a structural formula as shown in P1:
[0026] , where n is 20; The preparation method of the poly(thiophenylene benzothiazole) compound described in this Example 1 consists of the following steps: Add cesium carbonate (0.9 mmol, 293.2 mg), M1 (0.3 mmol, 51.0 mg) and 1 mL of DMF to a 10 mL dry polymerization tube equipped with a magnetic stir bar. Pipette carbon disulfide (0.72 mmol, 44 μL) into it, and the reaction system reacts at 25 °C for 1 hour. Subsequently, add copper(I) bromide (0.9 mmol, 129.1 mg), N1 (0.3 mmol, 135 mg) and 1 mL of DMF to the polymerization tube, and the reaction system reacts at 110 °C for 12 hours. After the reaction is completed, cool to room temperature, add 2 mL of DMF, and stir and dilute. Then, perform vacuum filtration on the obtained polymer solution. The filtrate is added dropwise to 150 mL of methanol stirred at 700 revolutions per minute to produce a precipitate, then let it stand, filter and collect the precipitate, and dry it at 90 °C to constant weight to obtain the poly(thiophenylene benzothiazole) compound P1.
[0027] The poly(thiophenylene benzothiazole) compound is prepared by a multi-component tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer and a bifunctional o-iodoaniline monomer, and the reaction equation is as shown in Equation (I): ; Among them, monomer M1 was commercially purchased; monomer N1 can be synthesized by referring to the preparation method in the literature (Macromolecules, 2021, 54(9):4112−4119).
[0028] Through measurement and analysis, the yield of the polysulfurized benzothiazole compound P1 was 72%, the weight-average molecular weight was 8800, and the molecular weight distribution was 1.43. The nuclear magnetic resonance hydrogen spectrum of the polysulfurized benzothiazole compound is shown in Figure 1 . Figure 1 In it, the characteristic peaks at chemical shifts of 7.92 - 6.80 ppm correspond to the hydrogen atoms on the benzene ring in the structure of the polysulfurized benzothiazole compound, the characteristic peaks at chemical shifts of 4.06 - 3.51 ppm correspond to the hydrogen atoms on the benzyl group connecting the benzene ring in the structure of the polysulfurized benzothiazole compound, and the characteristic peaks at chemical shifts of 4.68 - 4.07 ppm correspond to the hydrogen atoms on the adjacent methylene group of the condensed heterocycle in the structure of the polysulfurized benzothiazole compound. Figure 2 This is the ultraviolet absorption spectrum of the polysulfurized benzothiazole compound prepared in Example 1. It exhibits multiple broad absorption bands, which is attributed to the conjugated system of the benzothiazole condensed ring and the benzene ring in P1. The nuclear magnetic resonance hydrogen spectrum and the ultraviolet spectrum confirm the correctness of the structure of P1. The polysulfurized benzothiazole compound is easily soluble in organic solvents such as DMSO, DMF, and DMAc at room temperature, indicating excellent solubility. In addition, the thermogravimetric curve of the polysulfurized benzothiazole compound is shown in Figure 4 , and its T d temperature is 319 °C, indicating good thermal stability.
[0029] When 0.2% (percentage by mass of cement) of the polysulfurized benzothiazole compound P1 is added to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 21.5 cm, indicating that the effect of dispersing the cement paste by this polymer is obvious.
[0030] Example 2 For the polysulfurized benzothiazole compound described in this Example 2, its structural formula is as shown in P2: , where n is 16; The preparation method of the polythiophenobenzothiazole compound described in this Example 2 consists of the following steps: Add potassium carbonate (0.6 mmol, 82.9 mg), M2 (0.3 mmol, 45.0 mg) and 1 mL of DMF into a 10 mL dry polymerization tube equipped with a magnetic stir bar. Pipette carbon disulfide (0.78 mmol, 48 μL) into it, and the reaction system reacts at 30 °C for 0.5 hour. Subsequently, add copper(I) iodide (0.3 mmol, 57.1 mg), N1 (0.3 mmol, 135 mg) and 0.5 mL of DMF into the polymerization tube, and the reaction system reacts at 130 °C for 3 hours. After the reaction is completed, cool it to room temperature, add 2.5 mL of DMF, and stir for dilution. Then, perform vacuum filtration on the obtained polymer solution. Dropwise add the filtrate into 150 mL of methanol stirred at 700 revolutions per minute to produce precipitation, then let it stand, filter and collect the precipitate, and dry it to constant weight to obtain the polythiophenobenzothiazole compound P2.
[0031] The described polythiophenobenzothiazole compound is prepared by the polymerization reaction of carbon disulfide, bifunctional thiol monomers and bifunctional o-iodoaniline monomers, and the reaction equation is as shown in Equation (II): ; Among them, monomer M2 is commercially available; the synthesis method of monomer N1 is the same as that in Example 1.
[0032] After determination and analysis, the yield of the polythiophenobenzothiazole compound P2 is 58%, the weight-average molecular weight is 6700, and the molecular weight distribution is 1.32. This polythiophenobenzothiazole compound is easily soluble in organic solvents such as DMSO, DMF and DMAc at room temperature, indicating excellent solubility. The T d temperature is 286 °C, indicating good thermal stability.
[0033] When adding 0.2% (percentage by mass of cement) of the polythiophenobenzothiazole compound P2 to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 19.3 cm, indicating that the effect of dispersing the cement paste by this polymer is more obvious.
[0034] Example 3 The polythiophenobenzothiazole compound described in this Example 3 has the structural formula as shown in P3: , where n is 18; The preparation method of the poly(polythiophenylene benzothiazole) compound described in Example 3 consists of the following steps: Add cuprous bromide (0.6 mmol, 86.1 mg), cesium carbonate (0.9 mmol, 293.2 mg), and M3 (0.3 mmol, 75.0 mg) to a 10 mL dry polymerization tube equipped with a magnetic stir bar, and evacuate and refill with nitrogen three times. Then, add carbon disulfide (0.6 mmol, 37 μL) and 1 mL of DMF to the reaction system under a nitrogen atmosphere using a syringe, and react the reaction system at 30 °C for 2 hours. Subsequently, add N1 (0.3 mmol, 135 mg) and 0.5 mL of DMF to the polymerization tube, and react the reaction system at 100 °C for 8 hours. After the reaction is completed, cool to room temperature, add 2.5 mL of DMF, and stir to dilute. Then, perform vacuum filtration on the obtained polymer solution. The filtrate is added dropwise to 150 mL of methanol stirred at 700 revolutions per minute to produce a precipitate, and then allowed to stand. The precipitate is filtered and collected, and dried to a constant weight to obtain the poly(polythiophenylene benzothiazole) compound P3.
[0035] The described poly(polythiophenylene benzothiazole) compound is prepared by a multicomponent tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer, and a bifunctional o-iodoaniline monomer. The reaction equation is as shown in Equation (III): ; Among them, monomer M3 is commercially available; the synthesis method of monomer N1 is the same as that in Example 1.
[0036] After determination and analysis, the yield of the poly(polythiophenylene benzothiazole) compound P3 is 75%, the weight-average molecular weight is 9400, and the molecular weight distribution is 1.48. The ultraviolet absorption spectrum of this poly(polythiophenylene benzothiazole) compound is shown in Figure 3 . Figure 3 In, a broad absorption band is presented at 350 - 240 nm, which is attributed to the conjugated system of the polythiophenylene benzothiazole fused ring and the benzene ring in P3. This poly(polythiophenylene benzothiazole) compound is readily soluble in organic solvents such as DMSO, DMF, and DMAc at room temperature. Its thermogravimetric curve is shown in Figure 5 , and its T d temperature is 312 °C, indicating excellent solubility and thermal stability.
[0037] When 0.2% (percentage by mass of cement) of the poly(polythiophenylene benzothiazole) compound P3 is added to neat cement paste (Jiahua G-class oil well cement, water-solid ratio of 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 22.8 cm, indicating that the polymer has an obvious effect on dispersing the cement paste.
[0038] Example 4 The poly(polythiophenylene benzothiazole) compound described in this Example 4 has a structural formula as shown in P4: , wherein n is 17; The preparation method of the polysulfurized benzothiazole compound described in Example 4 of the present invention comprises the following steps: Add potassium phosphate (0.3 mmol, 63.7 mg), M1 (0.3 mmol, 51.0 mg) and 1 mL of DMF to a 10 mL dry polymerization tube equipped with a magnetic stirrer. Pipette carbon disulfide (0.54 mmol, 34 μL) into it, and the reaction system reacts at 10 °C for 2 hours. Subsequently, add cuprous chloride (0.6 mmol, 59.4 mg), N2 (0.3 mmol, 139.2 mg) and 1 mL of DMF to the polymerization tube, and the reaction system reacts at 120 °C for 18 hours. After the reaction is completed, cool to room temperature, add 2 mL of DMF, and stir and dilute. Then, perform vacuum filtration on the obtained polymer solution. The filtrate is added dropwise to 150 mL of methanol stirred at 700 revolutions per minute to produce a precipitate, and then left standing. The precipitate is filtered and collected and dried to a constant weight to obtain the polysulfurized benzothiazole compound P4.
[0039] The described polysulfurized benzothiazole compound is prepared by a multi-component tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer and a bifunctional o-iodoaniline monomer, and the reaction equation is as shown in Equation (IV): ;
[0040] Among them, monomer M1 is commercially available; monomer N2 can be synthesized with reference to the preparation method in the literature (Macromolecules, 2021, 54(9):4112−4119).
[0041] After determination and analysis, the yield of the polysulfurized benzothiazole compound P4 is 65%, the weight average molecular weight is 7600, and the molecular weight distribution is 1.39. This polysulfurized benzothiazole compound is easily soluble in organic solvents such as DMSO, DMF and DMAc at room temperature, indicating excellent solubility. The T d temperature is 322 °C, indicating good thermal stability.
[0042] When adding 0.2% (by weight of cement) of the polysulfurized benzothiazole compound P4 to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 21.9 cm, indicating that the effect of dispersing the cement paste by this polymer is obvious.
[0043] Example 5 The polysulfurized benzothiazole compound described in this Example 5 has a structural formula as shown in P5: , wherein n is 14; The preparation method of the polythiophenylene benzothiazole compound described in Example 5 consists of the following steps: Add cesium carbonate (0.15 mmol, 48.9 mg), M2 (0.36 mmol, 54.0 mg) and 0.5 mL of DMF into a 10 mL dry polymerization tube equipped with a magnetic stir bar. Pipette carbon disulfide (0.66 mmol, 41 μL) into the reaction system, and the reaction system reacts at 30 °C for 1 hour. Subsequently, add cuprous bromide (0.6 mmol, 86.1 mg), N2 (0.3 mmol, 139.2 mg) and 0.5 mL of DMF into the polymerization tube, and the reaction system reacts at 80 °C for 36 hours. After the reaction is completed, cool to room temperature, add 3 mL of DMF, and stir and dilute. Then, perform vacuum filtration on the obtained polymer solution. The filtrate is added dropwise to 150 mL of methanol stirred at 700 revolutions per minute to generate a precipitate, and then left standing. The precipitate is filtered and collected, and dried to a constant weight to obtain the polythiophenylene benzothiazole compound P5.
[0044] The described polythiophenylene benzothiazole compound is prepared by a multi-component tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer and a bifunctional o-iodoaniline monomer. The reaction equation is as shown in Equation (V):
[0045] Among them, monomer M2 is commercially available; the synthesis method of monomer N2 is the same as that in Example 4.
[0046] Through determination and analysis, the yield of the polythiophenylene benzothiazole compound P5 is 50%, the weight average molecular weight is 6000, and the molecular weight distribution is 1.26. This polythiophenylene benzothiazole compound is easily soluble in organic solvents such as DMSO, DMF and DMAc at room temperature, indicating excellent solubility. The T d temperature is 290 °C, indicating good thermal stability.
[0047] When adding 0.2% (percentage by mass of cement) of the polythiophenylene benzothiazole compound P5 to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 20.1 cm, indicating that the polymer has an obvious effect on dispersing the cement paste.
[0048] Example 6 The polythiophenylene benzothiazole compound described in this Example 6 has a structural formula as shown in P6: , whereinn is 18; The preparation method of the polysulfurized benzothiazole compound described in Example 6 consists of the following steps: Add cuprous chloride (1.2 mmol, 118.8 mg), cesium carbonate (0.6 mmol, 195.5 mg), and M3 (0.3 mmol, 75.0 mg) to a 10 mL dry polymerization tube equipped with a magnetic stir bar, and evacuate and replace with nitrogen three times. Then, add carbon disulfide (0.66 mmol, 41 μL) and 1 mL of DMF to the reaction system under a nitrogen atmosphere, and react the reaction system at 30 °C for 1 hour. Subsequently, add N2 (0.3 mmol, 139.2 mg) and 0.5 mL of DMF to the polymerization tube, and react the reaction system at 110 °C for 7 hours. After the reaction is completed, cool to room temperature, add 2.5 mL of DMF, and stir to dilute. Then, perform vacuum filtration on the obtained polymer solution. The filtrate is added dropwise to 150 mL of methanol stirred at 700 revolutions per minute to produce a precipitate, then let it stand, filter and collect the precipitate, and dry to a constant weight to obtain the polysulfurized benzothiazole compound P6.
[0049] The described polysulfurized benzothiazole compound is prepared by a multi-component tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer, and a bifunctional o-iodoaniline monomer, and the reaction equation is as shown in Equation (VI): ; Among them, monomer M3 is commercially available; the synthesis method of monomer N2 is the same as that in Example 4.
[0050] After measurement and analysis, the yield of the polysulfurized benzothiazole compound P6 is 86%, the weight average molecular weight is 9600, and the molecular weight distribution is 1.48. This polysulfurized benzothiazole compound is easily soluble in organic solvents such as DMSO, DMF, and DMAc at room temperature, indicating excellent solubility. The T d temperature is 315 °C, indicating good thermal stability.
[0051] When 0.2% (percentage by mass of cement) of the polysulfurized benzothiazole compound P6 is added to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 23.2 cm, indicating that the polymer has an obvious effect on dispersing the cement paste.
[0052] Example 7 The polysulfurized benzothiazole compound prepared in this Example 7 has a structural formula as shown in P7: , where n is 15; The preparation method of the polythiophenobenzothiazole compound described in Example 7 consists of the following steps: Add cesium carbonate (0.6 mmol, 195.5 mg), M1 (0.24 mmol, 40.8 mg) and 1 mL of DMF into a 10 mL dry polymerization tube equipped with a magnetic stirrer. Pipette carbon disulfide (0.66 mmol, 41 μL) into it, and the reaction system reacts at 25 °C for 1 hour. Subsequently, add copper(I) bromide (0.6 mmol, 86.1 mg), N3 (0.3 mmol, 184.2 mg) and 0.5 mL of DMF into the polymerization tube, and the reaction system reacts at 120 °C for 6 hours. After the reaction is completed, cool it to room temperature, add 2.5 mL of DMF, and stir to dilute. Then, perform vacuum filtration on the obtained polymer solution. Dropwise add the filtrate into 150 mL of methanol stirred at 700 revolutions per minute to produce precipitation. Then let it stand, filter and collect the precipitate, and dry it to constant weight to obtain the polythiophenobenzothiazole compound P7.
[0053] The described polythiophenobenzothiazole compound is prepared by a multi-component tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer and a bifunctional o-iodoaniline monomer. The reaction equation is as shown in Equation (VII):
[0054] Among them, monomer M1 is commercially available; monomer N3 can be synthesized by referring to the preparation method in the literature (Macromolecules, 2021, 54(9):4112−4119).
[0055] Through measurement and analysis, the yield of the polythiophenobenzothiazole compound P7 is 70%, the weight-average molecular weight is 8900, and the molecular weight distribution is 1.46. This polythiophenobenzothiazole compound is easily soluble in organic solvents such as DMSO, DMF and DMAc at room temperature, indicating excellent solubility. The T d temperature is 325 °C, indicating good thermal stability.
[0056] When adding 0.2% (percentage by mass of cement) of the polythiophenobenzothiazole compound P7 to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 22.5 cm, indicating that the effect of this polymer on dispersing cement paste is obvious.
[0057] Example 8 The polythiophenobenzothiazole compound prepared in this Example 8 has the structural formula as shown in P8: , where n is 12; The preparation method of the polythiophenobenzothiazole compound described in Example 8 consists of the following steps: Add cesium carbonate (0.6 mmol, 195.5 mg), M2 (0.3 mmol, 45.0 mg) and 1 mL of DMF into a 10 mL dry polymerization tube equipped with a magnetic stir bar. Pipette carbon disulfide (0.66 mmol, 41 μL) into it, and the reaction system reacts at 25 °C for 1 hour. Subsequently, add cuprous bromide (0.6 mmol, 86.1 mg), N3 (0.3 mmol, 184.2 mg) and 1 mL of DMF into the polymerization tube, and the reaction system reacts at 110 °C for 12 hours. After the reaction is completed, cool it to room temperature, add 2 mL of DMF, and stir and dilute. Then, perform vacuum filtration on the obtained polymer solution. Dropwise add the filtrate into 150 mL of methanol stirred at 700 revolutions per minute to generate a precipitate, then let it stand, filter and collect the precipitate, and dry it to constant weight to obtain the polythiophenobenzothiazole compound P8.
[0058] The described polythiophenobenzothiazole compound is prepared by a multi-component tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer and a bifunctional o-iodoaniline monomer, and the reaction equation is as shown in Equation (VIII): ; Among them, monomer M2 is commercially available; the synthesis method of monomer N3 is the same as that in Example 7.
[0059] After determination and analysis, the yield of the polythiophenobenzothiazole compound P8 is 68%, the weight average molecular weight is 7100, and the molecular weight distribution is 1.41. This polythiophenobenzothiazole compound is easily soluble in organic solvents such as DMSO, DMF and DMAc at room temperature, indicating excellent solubility. The T d temperature is 292 °C, indicating good thermal stability.
[0060] When adding 0.2% (percentage by mass of cement) of the polythiophenobenzothiazole compound P8 to neat cement paste (Jiahua G-class oil well cement, water-solid ratio is 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 21.4 cm, indicating that the effect of this polymer on dispersing cement slurry is obvious.
[0061] Example 9 The polythiophenobenzothiazole compound prepared in this Example 9 has the structural formula as shown in P9: , where n is 14; The preparation method of the poly(polythiophenylene benzothiazole) compound described in this Example 9 consists of the following steps: Add cuprous bromide (0.9 mmol, 129.1 mg), cesium carbonate (0.9 mmol, 293.2 mg), and M3 (0.3 mmol, 75.0 mg) to a 10 mL dry polymerization tube equipped with a magnetic stir bar, and evacuate and replace with nitrogen three times. Then, add carbon disulfide (0.66 mmol, 41 μL) and 1 mL of DMF to the reaction system under a nitrogen atmosphere using a syringe, and react the reaction system at 30 °C for 1 hour. Subsequently, add N3 (0.3 mmol, 184.2 mg) and 0.5 mL of DMF to the polymerization tube, and react the reaction system at 90 °C for 24 hours. After the reaction is completed, cool to room temperature, add 2.5 mL of DMF, and stir to dilute. Then, perform vacuum filtration on the obtained polymer solution. The filtrate is added dropwise to 150 mL of methanol stirred at 700 revolutions per minute to produce a precipitate, and then left standing. The precipitate is filtered and collected, and dried to a constant weight to obtain the poly(polythiophenylene benzothiazole) compound P9.
[0062] The described poly(polythiophenylene benzothiazole) compound is prepared by a multicomponent tandem polymerization reaction of carbon disulfide, a bifunctional thiol monomer, and a bifunctional o-iodoaniline monomer. The reaction equation is as shown in Equation (IX): ; Among them, monomer M3 is commercially available; the synthesis method of monomer N3 is the same as that in Example 7.
[0063] Upon determination and analysis, the yield of the poly(polythiophenylene benzothiazole) compound P9 is 81%, the weight-average molecular weight is 9700, and the molecular weight distribution is 1.52. This poly(polythiophenylene benzothiazole) compound is easily soluble in organic solvents such as DMSO, DMF, and DMAc at room temperature, indicating excellent solubility. The T d temperature is 318 °C, indicating good thermal stability.
[0064] When 0.2% (percentage by mass of cement) of the poly(polythiophenylene benzothiazole) compound P9 is added to neat cement paste (Jiahua G-class oil well cement, water-solid ratio of 0.44), the fluidity of the neat cement paste increases from 12.2 cm to 24.3 cm, indicating that the polymer has an obvious effect on dispersing the cement paste.
[0065] Comparative Example 1 Add potassium carbonate (0.9 mmol, 124.8 mg), M1 (0.3 mmol, 51.0 mg) and 1 mL of DMF into a 10 mL dry polymerization tube equipped with a magnetic stir bar. Pipette carbon disulfide (0.72 mmol, 44 μL) into it, and the reaction system reacts at 30 °C for 1 hour. Subsequently, add copper(II) chloride dihydrate (0.6 mmol, 91.5 mg), N1 (0.3 mmol, 135 mg) and 2 mL of DMF into the polymerization tube, and the reaction system reacts at 110 °C for 24 hours. After the reaction is completed, cool it to room temperature, add 2 mL of DMF, and stir for dilution. Then, perform vacuum filtration on the obtained polymer solution. Dropwise add the filtrate into 150 mL of methanol stirred at 700 rpm, a very small amount of precipitate is produced, then let it stand, filter and collect the precipitate, and dry it to a constant weight. The product yield is 2%. It shows that copper(II) chloride dihydrate is not suitable for this polymerization reaction.
[0066] Comparative Example 2 Add cesium carbonate (0.9 mmol, 293.2 mg), M1 (0.3 mmol, 51.0 mg) and 1 mL of DMSO into a 10 mL dry polymerization tube equipped with a magnetic stir bar. Pipette carbon disulfide (0.72 mmol, 44 μL) into it, and the reaction system reacts at 25 °C for 1 hour. Subsequently, add cuprous bromide (0.9 mmol, 129.1 mg), N1 (0.3 mmol, 135 mg) and 1 mL of DMSO into the polymerization tube, and the reaction system reacts at 110 °C for 12 hours. After the reaction is completed, cool it to room temperature, add 2 mL of DMSO, and stir for dilution. Then, perform vacuum filtration on the obtained polymer solution. Dropwise add the filtrate into 150 mL of methanol stirred at 700 rpm, a precipitate is produced, then let it stand, filter and collect the precipitate, and dry it to a constant weight to obtain 112 mg of the polymer. Test its weight-average molecular weight to be 6900, and the molecular weight distribution is 1.21. The 1H NMR spectrum of this polymer is shown in Figure 6 . Figure 6 In it, the integral area of the characteristic peak at the chemical shift of 3.50 - 4.50 ppm is 23.54, which is much higher than the theoretical value of 6, indicating that this polymer is not a pure theoretical product and has a high impurity content.
[0067] The above embodiments are only the preferred embodiments of the present invention, which are only used to explain the present invention rather than limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit and essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A polysulfurized benzothiazole compound, characterized in that: The general structural formula is shown in Formula (I): ; Wherein: n is an integer from 5 to 100; R1 is selected from any one of the following chemical structural formulas 1-2; R2 is selected from the following chemical structural formula 3; R3 is selected from any one of the following chemical structural formulas 4-6; ; Wherein, * represents the substitution position.
2. A method for preparing the polysulfurized benzothiazole compound according to claim 1, characterized in that: It is one of Method 1 or Method 2; wherein: Method 1: Add an alkali, a bifunctional aliphatic thiol monomer, and an organic solvent into a polymerization tube, then dropwise add carbon disulfide for a low-temperature reaction, and then add a catalyst, a bifunctional o-iodoaniline monomer, and an organic solvent into the polymerization tube for a polymerization reaction. After the reaction is completed, purify and dry the product to obtain a polysulfurized benzothiazole compound; Method 2: Under a nitrogen atmosphere, add a catalyst, an alkali, and a bifunctional aromatic thiol monomer into a polymerization tube, then dropwise add carbon disulfide and an organic solvent for a low-temperature reaction. Subsequently, add a bifunctional o-iodoaniline monomer and an organic solvent into the polymerization tube for a polymerization reaction. After the reaction is completed, purify and dry the product to obtain a polysulfurized benzothiazole compound.
3. The preparation method of the polysulfurized benzothiazole compound according to claim 2, characterized in that: The general structural formula of the described bifunctional aliphatic thiol monomer is shown in Formula (II): ; The general structural formula of the described bifunctional aromatic thiol monomer is shown in Formula (III): ; The general structural formula of the described bifunctional o-iodoaniline monomer is shown in Formula (IV): ; In the above Formulas (II)-(IV), R1 is selected from any one of the following chemical structural formulas 1-2; R2 is selected from the following chemical structural formula 3; R3 is selected from any one of the following chemical structural formulas 4-6; ; Wherein, * represents the substitution position.
4. The preparation method of the polysulfurized benzothiazole compound according to claim 2, characterized in that: In Method 1 or Method 2, the organic solvent is N,N-dimethylformamide. The organic solvent used in the low-temperature reaction is the same as the organic solvent used in the polymerization reaction, and their volume ratio is 1-2:1; the catalyst in Method 1 or Method 2 is one or more of cuprous chloride, cuprous bromide, or cuprous iodide.
5. The preparation method of the polysulfurized benzothiazole compound according to claim 2, characterized in that: The dosage of the catalyst in Method 1 or Method 2 is 1-4 times the amount of substance of the bifunctional o-iodoaniline monomer; The alkali in Method 1 or Method 2 is one or more of potassium carbonate, potassium phosphate, or cesium carbonate.
6. The preparation method of the polysulfurized benzothiazole compound according to claim 2, wherein: The dosage of the alkali in Method 1 or Method 2 is 0.5-3 times the amount of substance of the bifunctional o-iodoaniline monomer.
7. The preparation method of the polysulfurized benzothiazole compound according to claim 2, characterized in that: In Method 1, the molar ratio of carbon disulfide, the bifunctional aliphatic thiol monomer to the bifunctional o-iodoaniline monomer is (1.8 ~ 2.6):(0.8 ~ 1.2):1; In Method 2, the molar ratio of carbon disulfide, the bifunctional aromatic thiol monomer to the bifunctional o-iodoaniline monomer is (2.0 ~ 2.2):1:
1.
8. The preparation method of the polysulfurized benzothiazole compound according to claim 2, wherein: The concentration of the bifunctional o-iodoaniline monomer in the organic solvent in Method 1 or Method 2 is 0.15-0.3 mol / L.
9. The preparation method of the polysulfurized benzothiazole compound according to claim 2, characterized in that: In Method 1 or Method 2, the temperature of the low-temperature reaction is 10-30°C, the reaction time is 0.5-2 h, the temperature of the polymerization reaction is 80-130°C, and the reaction time is 3-36 h.
10. The preparation method of the polysulfurized benzothiazole compound according to claim 2, characterized in that: In Method 1 or Method 2, the purification and drying steps are as follows: the product after the polymerization reaction is dissolved in an organic solvent, filtered, and then the filtrate is added to one of methanol, n-hexane, petroleum ether, or ether for precipitation. The precipitate is collected and finally vacuum dried to a constant weight. Among them, the organic solvent in the purification step is the same as the organic solvent in the reaction system, and the drying temperature is 90 °C.
Citation Information
Patent Citations
Synthetic method of 2-mercaptobenzothiazole derivative
CN102911135A
2-mercapto benzothiazole derivative synthetic method with copper-catalyzed carbon disulfide
CN104098528A
Polycarbodiimide-based polymer, preparation method and applications thereof
CN107722262A
Synthesis method for preparing C-3-position thioimidazopyridine derivatives by copper-catalyzed one-pot method and application
CN110294757A
BIS-benzothiazolyl compounds
GB1323210A